A seguridade social dos indígenas brasileiros à luz dos direitos humanos e fundamentais - Freitas, Eduardo Marcelo de Negreiros (2016)
This research performs a study on the social security to Brazilian Natives, regarding the fundamental human rights. Thus, the social security subsystems are evaluated, however, to make this research detailed, it takes in consideration the Native’s Fundamental Human Rights, highlighting the historical evolution of these acquired rights by this minority, emphasizing the 1988 Brazilian Federal Constitution. In addition, it discusses aspects of monism and legal pluralism, normative provision of the Native Constitution and the Federal Constitution of 1988, including on fundamental rights, as well as ILO Convention 169 and the need of Brazil respecting the human rights treaties. So, it examines the role of the Native’s Social Security, starting by the general Social Security. It has contributory aspects, which differentiate, from, other areas. It discusses the correct framing of the natives on the list of obligatory insurance; and the aspects of all social security benefits due to the natives. A discussion about the health subsystem applicable to indigenous, highlighting the policies set by the Special Secretary of Indigenous Health (SESAI), which faces several difficulties, due to a lack of resources. Social assistance is studied in the policy of income transfer regarding the assistance benefits to elderly and people with special needs. Finally, it analyzes the challenges to the effectiveness of the fundamental rights, pointing administrative and legal aspects; also the need of a deeper study of this indigenous demand, given the existing peculiarities which can only be improved whether both FUNAI and its partners increase their activities; partners such as the Union Public Defender, the Federal Prosecutor and the Judicial Power, to secure the native’s fundamental rights. Today’s easy access to justice is an important key to the native’s rights public knowledge, however the lack of reasonable decisions might require actions by the Inter American Court of Human Rights to the final resolution of these indigenous demands.